Neutron polarisation analysis of Polymer:Fullerene blends for organic photovoltaics. (22nd November 2016) - Paternò, Giuseppe Maria; Stewart, J. Ross; Wildes, Andrew; Cacialli, Franco; Sakai, Victoria García
Abstract: The photogeneration process in polymer-fullerene organic solar cells relies strongly on the nanostructure and on the nano/picosecond dynamics occurring in these complex blends. Elastic and inelastic neutron scattering techniques are valuable tools with which to investigate those features in the appropriate time and space domains. In particular, quasi-elastic neutron scattering (QENS) connects useful structural and dynamical information by the measurement of dynamical incoherent (single particle) fluctuations in soft materials as a function of lengthscale. Extraction of these fluctuation rates can, however, be hampered by the presence of coherent contributions, originating from elastic scattering, and/or inelastic scattering modes which overlap in the space/time domain with the incoherent single-particle motions. As we have already seen in a previous study [1], this happens in poly(3-hexylthiophene) (P3HT) and [6, 6]-Phenyl C61 butyric acid methyl ester (PCBM) solid blends, in which the coherent contribution arising from the PCBM crystalline phase seems to affect the interpretation of the polymer dynamics. Here, we utilise neutron polarisation analysis as an effective tool to separate coherent and incoherent contributions and make QENS data analysis of these blends more reliable. Graphical abstract: Highlights: Neutron polarisation analysis on a QENS spectrometer is a promising tool. Separation of coherent elastic/inelastic signals key to interpret complex polymers. Dynamics of P3HT side-chains are slowed down by PCBM in solar cell formulations.